Max Headroom : the complete series [videorecording (DVD)] - Mann, Farhad; Frewer, Matt, 1958-; Pays, Amanda; Tambor, Jeffrey, 1944-; Young, Chris, 1971-; Coe, George (Shout! Factory, 2019)
After a television reporter is almost killed by his boss, a technology expert makes a copy of the reporter's mind and turns it into a character on a television screen.